ANALYSIS OF THE EFFECT OF EARNING PER SHARE (EPS) AND RETURN ON EQUITY (ROE) ON STOCK PRICES: A STUDY OF STATE-OWNED ENTERPRISE (BUMN) ISSUERS ON THE INDONESIA STOCK EXCHANGE IN THE 2015-2024 PERIOD - Nur Aliyah Marwah; Hety Budiyanti; Annisa Paramaswary Aslam (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to determine: (1) the effect of Earning Per Share (EPS) on stock prices in parent state-owned enterprise issuers, (2) the effect of Return on Equity (ROE) on stock prices in parent state-owned enterprise issuers, and (3) the effect of Earning Per Share (EPS) and Return on Equity (ROE) together on stock prices in parent state-owned enterprise issuers listed on the Indonesia Stock Exchange. This study uses a quantitative approach with an associative research type. The data used are secondary data obtained from annual financial reports and stock price data of parent state-owned enterprise issuers listed on the Indonesia Stock Exchange during the 2015–2024 period. The sampling technique was carried out by purposive sampling. The data analysis method used is panel data regression with the help of EViews software. The results of the study indicate that: (1) Earning Per Share (EPS) partially has a positive and significant effect on the stock price of parent BUMN issuers with a value (p-value 0.02 < 0.05), (2) Return on Equity (ROE) partially has a positive and significant effect on the stock price of parent BUMN issuers with a value (p-value 0.01 < 0.05), and (3) Earning Per Share (EPS) and Return on Equity (ROE) simultaneously have a significant effect on the stock price of parent BUMN issuers with a value (p-value 0.000 < 0.05). In addition, company size as a control variable also strengthens the relationship between the company's fundamental performance and stock prices.